A Review on the Evaporation Dynamics of Sessile Drops of Binary Mixtures: Challenges and Opportunities - Gurrala, Pradeep; Balusamy, Saravanan; Banerjee, Sayak; Chandra Sahu, Kirti (Fluid dynamics & materials processing, 2021)
The wetting and evaporation dynamics of sessile droplets have gained considerable attention over the last few years due to their relevance to many practical applications, ranging from a variety of industrial problems to several biological systems. Droplets made of binary mixtures typically undergo complex dynamics due to the differential volatility of the considered components and the ensuing presence of thermocapillary effects. For these reasons, many research groups have focused on the evaporation of binary droplets using a variegated set of experimental, numerical, and purely theoretical approaches. Apart from reviewing the state-of-the-art about the existing experimental, analytical, and computational techniques used to study the evaporation dynamics of binary sessile droplets, we also provide some indications about possible future research directions in this specific area.